Szczątki zwierząt ze stanowiska Poznań-Nowe Miasto, nr 362 - Osypińska, Marta (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2013)
The assemblage of 248 bone fragments and teeth was subjected to archaeo-zoological analysis. They were found in features 1,2, 61, 66 and 70, and dated to phases B and C of the Early Middle Ages and unearthed on site 362 in Poznań-Nowe Miasto (Tab. 2). In the assemblage of animal remains dated to phase B of the Early Middle Ages, 148 fragments in total were identified. The most frequent were those of cattle (Bos primigenius f. domestica – 43.91% – Tab. 3), followed by pigs (Sus scrofa f. domestica – 36.48%). By contrast, the least numerous group was that of the bone remains of small ruminants: mainly sheep (Ovis orientalis f. domestica) and, even less frequent, goat (Capra aegagrus f. domestica – 16.21% – Tab. 3). The last domesticated species identified was chickens (Gallus gallus f. domestica – 2.7%). Only a single bone fragment from a wild animal was recorded; it came from a roe deer (Capreolus capreolus – Tab. 3 ). The assemblage of bone remains dated to phase C contains only two identified bones. Both originated from the skeleton of a pig (Tab. 4). An analysis of the anatomical distribution of cattle remains, in line with the technical division of a carcass, showed cranial bone fragments to be the most numerous (43.07% – Tab. 7), followed by trunk bone fragments (18.46%), those of the proximal part of pelvic limbs (13.84%), proximal part of thoracic limbs and the distal part of pelvic limbs (10.76% each). In the case of pig remains, the greatest share also belonged to fragments originating from the head (Tab. 8). A relatively high incidence and percentage share also characterized bone fragments coming from the proximal part of thoracic limbs, proximal part of pelvic limbs as well as the trunk. In the case of small ruminants, head bone fragments were the most numerous. Also, several bone fragments of each of the following categories were identified: trunk, proximal parts of limbs, and the distal part of pelvic limbs (Tab. 9). The identification of the sex of animals was possible only with respect to pig remains – a single tooth from a female and two teeth from a male were recorded. The state of preservation of the animal remains from the site, specifically their advanced fragmentation, made osteometric analyses difficult. Only a few cattle bones and a single sheep bone had their metric characteristics preserved. In no case was it possible to calculate their height at shoulder level. Only the application of the point method helped estimate the morphology of the cattle used on the site in the 7th- 8th century. The results show the cattle to vary morphologically: medium-height varieties, having an estimated height at shoulder of about 108-110 cm, are mixed with tall varieties, perhaps having the characteristics of ‘primigenius’ cattle, with an estimated height of 138 cm. Most of the damage recorded on the animal bones from the site was done in the second taphonomic phase, i.e. after they had been discarded (in most cases these were traces of gnawing by dogs) (Tab. 11). A few traces left in the first phase were also identified. They included notches, traces of chopping, a hole bored in a proximal epiphysis to extract marrow (Photo 2-4), as well as traces of singeing and charring (Tab. 11). In addition, a small awl, made from a roe deer radius, was identified in the fill of the destroyed semi-dugout (inv. no. 51/09) (Tab. 11; Photo 1).